Mortality in Chicks Associated with Economic Impact and Prospect of Layer Chick Rearer Package Programme of the Participatory Livestock Development Project in Bangladesh - Islam, M.T.; Samad, M.A. (International Journal of Poultry Science, 2004)
The Participatory Livestock Development Project (PLDP) has been implemented in Bangladesh for the alleviation of poverty through livestock production, employment, income generation and intake of nutrition in rural people. The management and disease problems with cost-benefit analysis of the layer chick rearer package programme of the PLDP have been evaluated in randomly selected 10 layer chick rearing units (n=3100 chicks) from day-old chicks up to 60 days to marketing of Muktagacha areas in the district of Mymensingh during the period from August to December 2002. It appears from the results of this study that 12.87% chicks died within 60 days of age inspite of chick reared in intensive management system and provided vaccines against common infectious diseases. The diagnosed diseases associated with mortality of chicks included infectious bursal disease (37.6%), coccidiosis (13.28%), chronic respiratory disease (13.28%) and other conditions (35.84%). The highest mortality rate (37.6%) in layer chicks, caused by infectious bursal disease (IBD), which were double vaccinated with Nobilis® Gumboro D-78 vaccines (Intervet) that indicates vaccination failure against IBD which deserve further investigation. Cost-benefit analysis of the outcome of the 10 layer chick rearing units varied, and it was found loss in one unit (-3.17%) and the highest profit of 45.66% with an average profit of 27.33%. However, profit was recorded in all the layer chick rearing units except one unit due to outbreak of IBD which could be due to vaccination failure. Therefore, it may be concluded from the results of this study that the ‘layer chick rearer package programme` could be economically prospective for the alleviation of poverty of rural people if the major infectious diseases of poultry are controlled in Bangladesh.